Thermodynamic Performance Analysis of a Parabolic Trough Solar-assisted Biomass-fired Cogeneration System - Kai XUE; Yihan WANG; Heng CHEN; Gang XU; Jing LEI (发电技术)
The integration of renewable energy combined heat and power system has broad application prospects in the field of regional comprehensive energy utilization. This paper proposed a parabolic trough solar-assisted biomass-fired cogeneration system. The system uses medium and low temperature trough solar energy to heat the thermal oil that drives the absorption heat pump to preheat the supply-water, while the biomass fuel and heat output keep constant. The extraction steam for heating is decreased while power generation is increased. The EBSILON professional software was used to model and simulate the case plant and integrated system, and on this basis, the thermodynamic characteristics of energy flow and exergy loss of the system were analyzed. The results show that, under the design conditions, 1.78 MW·h of solar power can be generated, the solar-to-electricity efficiency is 20.06%, and the solar-to-electricity exergy efficiency can reach 21.60%. Five typical days were selected to explore the performance under different radiation conditions. We found that the solar radiation and system performance on March 21st are both the best. A time-by-hour simulation analysis was conducted for the entire heating season. A total of 1 124.30 MW·h of solar power is produced in the five-month heating period with an average solar-to-electricity efficiency of 16.49%.